Modelo alométrico para estimar la altura total de las especies forestales del bosque de terraza alta de la comunidad campesina Tres Hermanos del Bajo Tapiche, distrito de Requena, Loreto, 2022 - Correa Vásquez, José Miguel (2023)
A high terrace forest was chosen in the district of Requena, Loreto, Peru, in order to use the allometric model to evaluate the total height of forest species. Data from the forest census of commercial species were evaluated in order to obtain permits for logging in rural areas. The mean diameter-total tree height connection was found to be well fitted by the cubic-type distribution model Y = 29,468 + (-0,135 x DBH) + (0,000 x DBH2) + (5,630E-6 x DBH3), with a correlation coefficient of r=0,556 and a coefficient of determination of R2=0,309. The theory that the linear allometric model could not fit the relationship between diameter and total height to estimate tree height in the high terrace forest is rejected.